2017
DOI: 10.3390/ijms18091978
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Heat Shock Proteins in Cancer: A Promising Therapeutic Approach

Abstract: Heat shock proteins (HSPs) are a large family of chaperones that are involved in protein folding and maturation of a variety of “client” proteins protecting them from degradation, oxidative stress, hypoxia, and thermal stress. Hence, they are significant regulators of cellular proliferation, differentiation and strongly implicated in the molecular orchestration of cancer development and progression as many of their clients are well established oncoproteins in multiple tumor types. Interestingly, tumor cells ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
288
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 413 publications
(317 citation statements)
references
References 294 publications
4
288
0
Order By: Relevance
“…This role is clearly exposed when we describe both kinases and STAT proteins as HSP90 client proteins. The current literature points to the important role of HSP90/STAT3/STAT5 in cancer growth and the ability to thwart chemotherapy [3,[196][197][198].…”
Section: Discussionmentioning
confidence: 99%
“…This role is clearly exposed when we describe both kinases and STAT proteins as HSP90 client proteins. The current literature points to the important role of HSP90/STAT3/STAT5 in cancer growth and the ability to thwart chemotherapy [3,[196][197][198].…”
Section: Discussionmentioning
confidence: 99%
“…The inability of 17-AAG to protect SH-SY5Y cells from proteasome stress observed in our experiments might be explained by lower extent of Hsp70 induction after pretreatment of the cells with 17-AAG as compared to the levels of Hsp70 induced by CoCl 2 . On contrary, despite induction of protective Hsp70 17-AAG exhibits also cytotoxic effects and was tested for treatment of different cancers (Chatterjee and Burns 2017). Although, we did not incubate cells simultaneously with 17-AAG and bortezomib, it is important to note that combination of 17-AAG with bortezomib was associated with synergistic cell death effect on U266 (Duus et al 2006) and MCF-7 (Mimnaugh et al 2004)…”
Section: Discussionmentioning
confidence: 97%
“…Examining all HSPs identified in this study, we found that 20 HSPs were identified in spermathecae overall and only 13 were identified in the semen (Fig 6); however, the precise functions of specific honey bee HSPs are largely unknown. By contrast, mammalian HSPs have been studied extensively; research on human sHSPs has focused on their roles in many types of cancer (osteosarcoma, leukemia, breast, colorectal, hepatic, gastric, and prostate cancer) 59,60 , where their upregulation is associated with both pro-and anti-apoptotic properties and mitigating ROS production 54,57,61,62 .…”
Section: Figure 3 Heat-shock Does Not Affect Expression Of Superoxidmentioning
confidence: 99%